Outcomes of Women With Atypical Glandular Cells on Preoperative Cytology and Endometrial Cancer. Issue 2 (1st February 2014) - Guy, Michael S.; Cheng, Georgina; Post, Miriam D.; Spillman, Monique A.; Behbakht, Kian; Davidson, Susan; Sheeder, Jeanelle; Guntupalli, Saketh R.
Abstract : Objective: This study aims to examine the prognostic importance of preoperative cervical cytologic diagnosis with atypical glandular cells (AGC) or malignant cells (MC) as a predictor of poor outcomes in endometrial cancer. Materials and Methods: A total of 563 patients were surgically staged for endometrial adenocarcinoma from 2002 to 2012 at our institution. Of these patients, 106 were included to perform a case-control study (39 patients with AGC or MC and 67 controls). Included patients were not significantly different from excluded patients and were matched for age, race, and body mass index. Outcome variables included presence of extrauterine disease (International Federation of Gynecology and Obstetrics stage ≥II) and high intermediate risk (HIR) disease. Further analysis sought to improve the prediction combining AGC or MC with other factors, such as grade and CA-125 levels. Standard statistical analyses were used. Results: Among the patients with AGC or MC, 53.8% had HIR disease compared with 30.3% with normal cervical cytologic diagnosis (odds ratio [OR], 2.68; 95% confidence interval [CI], 1.18–6.09; P = 0.02). Extrauterine disease was found in 43.6% of patients with AGC or MC compared with that of 15.2% in patients with normal cervical cytologic diagnosis (OR, 4.33; 95% CI, 1.72–10.90; P < 0.01). Multivariate analysis confirmed that AGC or MC was an independent predictor of HIR disease (OR, 8.41; 95% CI, 1.34–52.78; P = 0.02) and extrauterine disease (OR, 4.78; 95% CI, 1.26–18.1; P = 0.02). The combination of elevated CA-125 levels with AGC or MC cervical cytologic diagnosis increased the statistical prediction of extrauterine disease (OR, 13.3; 95% CI, 3.1–56.8; P < 0.01) and HIR disease (OR, 5.83; 95% CI, 1.44–23.71; P = 0.02). Conclusions: Patients with AGC or MC on preoperative cervical cytology are at risk for extrauterine and HIR disease. These preoperative findings should warn surgeons of the potential of extrauterine or occult metastatic disease.